Cloning of the altered mRNA stability (ams) gene of Escherichia coli K-12. - Claverie-Martin, F (1989)
A temperature-sensitive mutation in the ams gene of Escherichia coli causes an increase in the chemical half-life of pulse-labeled RNA at the nonpermissive temperature. Using lambda clones containing DNA fragments from the 23- to 24-min region on the E. coli chromosome, we have isolated a 5.8-kilobase DNA fragment which, when present in a low-copy-number plasmid, complements the conditional lethality and increased mRNA stability associated with the ams-1 mutation. The approximate initiation site and the direction of transcription of the ams gene were determined from the size of truncated polypeptides produced by Tn1000 insertions and Bal 31 deletions. Overexpression of the ams locus by using a T7 RNA polymerase-promoter system permitted the identification of an ams-encoded polypeptide of 110 kilodaltons.